Synthesis, Spectral, and In Vitro Antibacterial Studies of Organosilicon(IV) Complexes with Schiff Bases Derived from Amino Acids - Har Lal Singh; Jangbhadur Singh; A. Mukherjee (Bioinorganic Chemistry and Applications)
The present work stems from our interest in the synthesis, characterization, and antibacterial evaluation of organosilicon(IV) complexes of a class of amino-acid-based Schiff base which have been prepared by the interaction of ethoxytrimethylsilane with the Schiff bases (N OH) in 1 : 1 molar ratio. These complexes have been characterized by elemental analysis, molar conductance, and spectroscopic studies including electronic IR and NMR (1H, 13C, and 29Si) spectroscopy. The analytical and spectral data suggest trigonal bipyramidal geometry around the silicon atom in the resulting complexes. The ligands and their organosilicon complexes have also been evaluated for in vitro antimicrobial activity against bacteria (Bacillus cereus, Nocardia spp., E. aerogenes, Escherichia coli, Klebsiella spp., and Staphylococcus spp.). The complexes were found to be more potent as compared to the ligands.